A simple staging system using biomarkers for wild‐type transthyretin amyloid cardiomyopathy in Japan. (22nd February 2022) - Nakashima, Naoya; Takashio, Seiji; Morioka, Mami; Nishi, Masato; Yamada, Toshihiro; Hirakawa, Kyoko; Ishii, Masanobu; Tabata, Noriaki; Yamanaga, Kenshi; Fujisue, Koichiro; Sueta, Daisuke; Kanazawa, Hisanori; et al.
Abstract: Aims: It has been reported that a staging system combining N‐terminal pro‐B‐type natriuretic peptide and high‐sensitivity troponin T (hs‐cTnT) or estimated glomerular filtration rate (eGFR) is useful in patients with wild‐type transthyretin amyloid cardiomyopathy (ATTRwt‐CM). However, these studies were mainly conducted in Western countries, and their usefulness for the Japanese population is unclear. We examined and validated the staging system using hs‐cTnT, eGFR, and B‐type natriuretic peptide (BNP) in Japanese patients with ATTRwt‐CM. Methods and results: We retrospectively evaluated 176 patients with ATTRwt‐CM. The cut‐off values of hs‐cTnT and eGFR were selected as 0.05 ng/mL and 45 mL/min/1.73 m 2, respectively, based on a previous report. The optimal cut‐off value of BNP was 255.6 pg/mL to predict all‐cause mortality (sensitivity, 75%; specificity, 58%; area under the curve, 0.69; 95% confidence interval [CI], 0.61–0.78; P  < 0.001) based on a receiver operating characteristic curve. We defined the cut‐off value of BNP as 250 pg/mL. Increased hs‐cTnT (>0.05 ng/mL) and BNP (>250 pg/mL) and decreased eGFR (<45 mL/min/1.73 m 2 ) were significant predictors of poor prognosis ( P  < 0.05). We calculated the score by adding 1 point if hs‐cTnT and BNP levels increased or eGFR decreased by more than the cut‐off value. The hazard ratio of all‐cause death adjusted by age and sex, using score 0 as a reference, was 0.44 (95% CI 0.08–2.49, P  = 0.44) for score 1, 3.69 (95% CI 1.21–11.21, P  = 0.02) for score 2, and 5.40 (95% CI 1.57–18.54, P  = 0.007) for score 3. We divided patients into a low score group (0–1 point) and high score group (2–3 points). Kaplan–Meier analyses revealed significant differences in all‐cause death and rehospitalization for heart failure (log rank test; P  < 0.001), and after adjusting for sex and age, the hazard ratio of all‐cause death was 6.96 (95% Cl 2.88–16.83, P  < 0.001) and that for rehospitalization for heart failure was 4.27 (95% Cl 2.26–8.07, P  < 0.001) in the high‐risk group, compared with those in the low‐risk group. The median survival period was 32.0 months in the high‐risk group. Conclusions: This simple staging system, which combines hs‐cTnT, BNP, and eGFR, was useful for predicting prognosis in Japanese patients with ATTRwt‐CM. This system can objectively evaluate the disease progression of ATTRwt‐CM and may be useful for patient selection for disease‐modifying therapy.